Relationship Between Islamic Financial Literacy, Islamic Financial Inclusion and Business Performance : Evidence from Culinary Cluster of Creative Economy - Trianto, Budi; Barus, Elida elfi; Sabiu, Tasiu Tijjani (IKONOMIKA, 2021)
The culinary cluster of creative economy in Indonesia has a strong appeal to business actors, so that business growth in the culinary cluster is always above other clusters. But unfortunately, the level of Islamic financial literacy and Islamic financial inclusiveness has not been created properly in this cluster. This study aims to see the relationship between Islamic financial literacy, Islamic financial inclusion and business growth in the culinary cluster of creative economy. The sample in this study was 62 business actors in the culinary cluster. To see this relationship, data were analyzed using the SEM-GeSCA approach. The results of this study indicate that Islamic financial literacy has a positive and significant impact on Islamic financial inclusion and business growth. Other research results also show a positive and significant impact relationship between Islamic financial inclusion and business growth. This result implies that business actors in the culinary cluster must continue to improve Islamic financial literacy and Islamic financial inclusion so that sustainable growth of their business can be created.